Exploring Writing Difficulties in Recount Texts Among Eighth-Grade Students at SMP Nasrani 5 Medan - Gracia Natalia Zamili; Siti Aminah Hasibuan; Fatin Nadifa Tarigan (Talenta Publisher, 2026)
This study aims to analyze the difficulties experienced by eighth-grade students in writing recount texts at SMP Nasrani 5 Medan. This research employed a descriptive qualitative method to obtain an in-depth understanding of students’ writing problems. The subjects of this study were eighth-grade students. The data were collected through writing tests and interviews. In the data collection process, students were first given an explanation of recount texts and their generic structure. Then, they were asked to write a recount text based on a selected topic within a limited time. The findings revealed that students encountered several difficulties in writing recount texts. These difficulties were mainly related to limited vocabulary, lack of grammatical mastery (including sentence structure, use of nouns and verbs), and insufficient understanding of the characteristics and organization of recount texts. In addition, some students had difficulty generating ideas and organizing them coherently. These problems affected the overall quality of their writing. Based on these findings, it is suggested that teachers apply more effective, structured, and engaging teaching strategies to improve students’ writing skills, particularly in composing recount texts.